Association Between Parity and Low Bone Density Among Postmenopausal Korean Women - Eunsun Seo; Yongrong Lee; Hyeon Chang Kim (Korean Society for Preventive Medicine, 2021)
Objectives Low bone density (LBD) in the postmenopausal period has long been a pervasive public health concern; however, the association between parity and LBD has yet to be fully elucidated. Thus, we investigated the association between parity and LBD in postmenopausal Korean women. Methods This study used baseline data from 1287 Korean postmenopausal women aged 40 years or older enrolled in the Cardiovascular and Metabolic Diseases Etiology Research Center community-based cohort study conducted in Korea from 2013 to 2017. The main exposure was parity (nullipara, 1, 2, 3+). The main outcome was LBD, including osteopenia and osteoporosis, based on bone mineral density measured using quantitative computed tomography of the lumbar spine (L1-2). Results The mean age of participants was 57.1 years, and the median parity was 2. Of the 1287 participants, 594 (46.2%) had osteopenia and 147 (11.4%) had osteoporosis. No significant difference in the prevalence of LBD was found between nullipara and parous women, whereas higher parity was associated with a higher risk of LBD among parous women; the adjusted odds ratio (95% confidence interval) for the presence of LBD was 1.40 (0.97 to 2.02) for a parity of 2 and 1.95 (1.23 to 3.09) for a parity of 3 relative to a parity of 1. Conclusions Women who have given birth multiple times may be at greater risk of bone loss after menopause; therefore, they should be a major target population for osteoporosis prevention.